Characterization of Crystal-Originated Particles in Silicon Nitride Doped, CZ-Grown Silicon Wafers - Lee, W. P.; Yow, H. K.; Tou, T. Y. (2006)
Grown-in crystal-originated particles (COPs) on the surface of silicon nitride-doped Czochralski (CZ)-grown silicon wafers were characterized using atomic force microscopy and scanning electron microscopy. These nanometer-scale COPs are categorized into kite-shaped, parallelepiped- plate and needle-shaped COPs, respectively, with unique features distinctively different from the octahedral voids commonly found in conventional CZ-grown silicon wafers. Based on the experimental data obtained, it is postulated that nitrogen dopants in the silicon crystals could influence the formation of these COPs with different morphologies and sizes. This may be supported by a simple analysis of the mapping distribution of COPs on the nitride-doped CZ-grown silicon wafer, which reveals that the densities of the smaller-size parallelepiped- plate and needle-shaped COPs are negligible at the center of the silicon wafer but increase to a significant proportion comparable to that of the kite-shaped COPs at the outer edges of the silicon wafer along the radial directions. These observations are thought to correlate well with the presence of nitrogen dopants and the radial concentrations of the excess free vacancy. (c) 2006 The Electrochemical Society.